Temperature and Pressure Dependence of the Raman Intensity and Frequency of a Soft Mode Near the Tricritical Point in the Ferroelectric Sbsi - Yurtseven, Hasan Hamit; Duman, Sinem; Duman, Sinem (Taylor & Francis, 2016)
We analyze the pressure dependence of the intensity and the frequency of a soft mode from the Raman and elastic light scattering experiments as reported in the literature close to the ferroelectric - paraelectric transition in SbSI crystal. The Raman intensity of this mode is analyzed as a function of pressure at constant temperatures of 272K (first order transition) and 234K (tricritical or second order transition) according to a power-law formula. Our analysis of the Raman intensity gives closely the mean field values for the order parameter. From our analysis, we also obtain that the Raman frequency (squared) of the soft mode varies linearly with the pressure at constant temperatures close to the ferroelectric - paraelectric transition in SbSI as obtained experimentally.
Keywords: Raman intensity and frequency; Soft model; Tricritical point; Ferroelectric SbSI